Land Rights and Expropriation in Ethiopia - Ambaye, Daniel W (Springer, 2015)
This thesis provides a new approach to the Ethiopian Land Law debate. The basic argument made in this thesis is that even if the Ethiopian Constitution provides and guarantees common ownership of land (together with the state) to the people, this right has not been fully realized whether in terms of land accessibility, enjoyability, and payment of fair compensation in the event of expropriation.